One China Policy sebagai Upaya China Menuju Kekuatan Global di Kawasan Indo-Pasifik - Muhammad Fathir Furqan; Darwis Darwis; Imam Fadhil Nugraha (Lembaga Pengembangan Kinerja Dosen, 2025)
China first established its mission to become a superpower in the year 2000, when they began implementing an open-ended trading system, where they implemented all of that in order to be able to equal or exceed the power of the United States in the coming years, one way is by expanding its influence in the Indo-Pacific region, where the region is one of the world's trading centers, in which the country of China stands, so that China can launch its mission more easily. Working with ASEAN and the South Pacific countries, developing trade cooperation, and providing support to specific countries for economic development are some of their methods. The